ASSESSMENT OF APPLE AND CARROT POMACES FOR COST-EFFECTIVE REACTIVE BLACK 5 BIOREMOVAL BY PENICILLIUM CITRINUM - Ekin Demiray (Journal of the Chilean Chemical Society, 2020)
In this study, Reactive Black 5 bioremoval by Penicillium citrinum was investigated. Common agricultural by-products of the food industry, such as apple and carrot pomaces were used as carbon sources.  Carrot and apple pomace were pretreated hydrothermally, and the effects of some critical parameters such as pH, initial biomass and dye loadings on Reactive Black 5 bioremoval were investigated. P. citrinum removed 80.87% of the dye in the presence of 16% carrot pomace, pH 5 and 225.9 mg/L initial dye loading, respectively. The maximum specific dye uptake rate was found as 52.92 mg/g under the same conditions. Moreover, notably bioremoval was observed even in high Reactive Black 5 concentrations such as 758.2 mg/L. The results showed that P. citrinum is suitable microorganism for dye removal, and carrot and apple pomaces can be evaluated for microbial growth as a cheap carbon source.